2010
DOI: 10.1111/j.1365-2842.2010.02186.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of additional mental foramina through cone beam computed tomography

Abstract: Variations in jaw bone neurovascularisation must be identified to decrease the potential risk for haemorrhages and neural disturbances during surgical procedures such as implant placement and orthognatic surgeries. The aim of this study is to characterise additional mental foramina (AMF) through cone beam computed tomography (CBCT) images, by describing their frequency, size, location and direction of their associated bony canals, as well as to assess their corresponding ipsilateral and contralateral mental fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
46
3
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 15 publications
5
46
3
2
Order By: Relevance
“…This way, the use of CBCT enables the dentist to obtain the details needed for the diagnosis and treatment planning or surgery. 12,13,15,16,17 The search for studies on the CS in the PubMed database detected only seven articles, four of which 11,15,16,17 used CBCT for better evaluation of anatomical variation. The present study assessed 500 CBCT scans with the intention of locating the CS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This way, the use of CBCT enables the dentist to obtain the details needed for the diagnosis and treatment planning or surgery. 12,13,15,16,17 The search for studies on the CS in the PubMed database detected only seven articles, four of which 11,15,16,17 used CBCT for better evaluation of anatomical variation. The present study assessed 500 CBCT scans with the intention of locating the CS.…”
Section: Discussionmentioning
confidence: 99%
“…11 CBCT is then indicated because it provides precise details of the studied region and eliminates overlapping images, in addition to collecting reliable linear and angular measurements and allowing reconstruction of the image in several planes and in 3D. 12 Thus, the aim of this study was to assess the presence, location, and multiplanar distance of the CS between the incisive foramen and the anterior maxillary alveolar ridge using CBCT.…”
Section: Introductionmentioning
confidence: 99%
“…Jacobs et al [6] reported that among 545 panoramic radiographies studied, the mental foramina were detected in 94 % of the cases and only 49 % were properly seen. Oliveira-Santos et al [10] have characterized additional mental foramin through CBCT images, by describing their frequency, size, location and direction of their associated bony canals, as well as to assess their corresponding ipsilateral and contralateral mental foramina. Panoramic radiography alone does not then seem to be reliable for accurate location of the mental foramen.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomy of the human mandible has been widely studied by means of advanced imaging technologies such as cone beam computed tomography (CBCT) [1][2][3][4], which is able to provide accurate, essentially immediate and non-invasive 3D radiographic images of teeth, soft-tissues, nerve paths and bone structures in the craniofacial region. With the growing morphology studies using 3D imaging in vivo or in vitro, in combination with increasingly sophisticated computer graphics applications, it also shows potentials of CBCT in the application of comparative anatomy, anthropology and forensic medicine for paleontologists [5][6][7].…”
Section: Introductionmentioning
confidence: 99%